The Tabula of Cebes as an Example of Allegorical Popularization of Ethics in Antiquity - Pacewicz, Artur (Peitho. Examina Antiqua, 2010)
The present paper offers a general introduction to the first Polish post¬war translation of the Tabula of Cebes. It discusses the general structure of the text and its major arguments. Subsequently, some speculations on the philosophical affinity of the author of the text are given and the nature of its reception is dealt with. Furthermore, the article presents also a brief history of allegorical interpretation in Greece and touches upon the most important exegetical tendencies that hitherto have appeared in European culture. The article is followed by the first Polish postwar translation of the Tabula of Cebes.